Rotura hepática en gestante residente en gran altura y la utilidad del monitoreo hemodinámico con doppler transesofágico - Tinoco-Solorzano, A. (2019)
ABSTRACT Hepatic rupture is a rare complication of pregnancy associated with preeclampsia and HELLP syndrome, thus increasing maternal morbidity and mortality. There are no reported cases of this condition in high-altitude dweller pregnant women, even though altitude is considered a factor that influences in pregnancy. In this article the case of a pregnant dweller at high altitude is reported, which revealed hepatic rupture with persistent bleeding, being reoperated by Emergency Surgery appropriately thanks to the hemodynamic monitoring with transesophageal Doppler.